2016
DOI: 10.1371/journal.pgen.1006133
|View full text |Cite
|
Sign up to set email alerts
|

DLK-1, SEK-3 and PMK-3 Are Required for the Life Extension Induced by Mitochondrial Bioenergetic Disruption in C. elegans

Abstract: Mitochondrial dysfunction underlies numerous age-related pathologies. In an effort to uncover how the detrimental effects of mitochondrial dysfunction might be alleviated, we examined how the nematode C. elegans not only adapts to disruption of the mitochondrial electron transport chain, but in many instances responds with extended lifespan. Studies have shown various retrograde responses are activated in these animals, including the well-studied ATFS-1-dependent mitochondrial unfolded protein response (UPRmt)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
84
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(98 citation statements)
references
References 118 publications
13
84
1
Order By: Relevance
“…is known to regulate longevity induced by mitochondrial disruption and axonal regeneration pathways 50,51 , consistent with our overall observations in cells and the ROS induction observed in the nematode. However, knockdown of pmk-3 canonical upstream control dlk-1 did not influence lactate-or pyruvate-mediated stress resistance ( Supplementary Fig.…”
Section: Eleganssupporting
confidence: 91%
“…is known to regulate longevity induced by mitochondrial disruption and axonal regeneration pathways 50,51 , consistent with our overall observations in cells and the ROS induction observed in the nematode. However, knockdown of pmk-3 canonical upstream control dlk-1 did not influence lactate-or pyruvate-mediated stress resistance ( Supplementary Fig.…”
Section: Eleganssupporting
confidence: 91%
“…Changes in animal metabolism, the induction of protective and detoxifying systems (e.g., mtUPR, antioxidants, autophagy) [7,[13][14][15][16], a smaller germline, a decreased but prolonged fertility, and a reduced adult size (often accompanied by slower development) are all associated with lifespan extension upon mitochondrial disturbance. Moreover, different molecular players have been identified in the past two decades that mediate Mit mutants' longevity: a handful of transcription factors [7,[17][18][19][20][21][22], autophagy-and apoptosis-regulatory genes [7,14,18,23,24], some kinases [25][26][27], as well as some mitochondrial metabolites [28] and chromatin remodeling genes [29,30]. Nonetheless, whether the same molecular mechanisms underlie the different Mit-mutant's phenotypic features is largely unknown [14,31,32].…”
Section: Introductionmentioning
confidence: 99%
“…This model reflects the well-established redundancy in the DNA damage response network 22 . Several recent studies by us and others 13, 36, 37 , have shown a role for MAPK signaling following ETC disruption in worms. Interestingly, the p38 MAPK-activated protein kinases MAPKAP-2 and MAPKAP-3 are checkpoint proteins known in humans to act in parallel to ATM and ATR 38, 39, 40 .…”
Section: Resultsmentioning
confidence: 83%
“…We next tested whether loss of atl-1 affected the activity of major stress response pathways known to be activated by atp-3 or isp-1 depletion 3, 13, 35, 56 . Loss of atl-1 did not result in constitutive activation of P hsp-6::GFP , P gst-4::GFP or P tbb-6::GFP , which are markers of ATFS-1, SKN-1/NRF-2 and PMK-3/p38 activation, respectively ( Supplemental Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation